Global education in manufacturing - Rolstadas, Asbjorn (Managing global transitions, 2006)
Many new challenges and opportunities have arisen for Slovenia since May 2004 when it became a full member of the EU. On the one hand we have some successful economic players who can definitely gain from new opportunities, on the other hand some structural changes still have to be accomplished. One of the most demanding tasks is related to higher education and in particular to harmonization of EU and global educational systems. The paper presents the results of the international framework for a Master degree curriculum in manufacturing strategy and an example of the integration of competence in technology and business. A good example of meeting Bologna goals is to establish a system of easily recognisable and comparable educational degrees and to accelerate the employment of EU citizens as well as the competitiveness of the European higher educational system.
Keywords: industrija; management; proizvodnja; izobraževanje; education; razvojna strategija